2019
DOI: 10.3390/condmat4040084
|View full text |Cite
|
Sign up to set email alerts
|

Dzyaloshinskii–Moriya Coupling in 3d Insulators

Abstract: We present an overview of the microscopic theory of the Dzyaloshinskii-Moriya (DM) coupling in strongly correlated 3d compounds. Most attention in the paper centers around the derivation of the Dzyaloshinskii vector, its value, orientation, and sense (sign) under different types of the (super)exchange interaction and crystal field. We consider both the Moriya mechanism of the antisymmetric interaction and novel contributions, in particular, that of spin-orbital coupling on the intermediate ligand ions. We have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 134 publications
3
49
0
Order By: Relevance
“…In-plane (dashed curve) and out-of-plane (full curve) zone-center energy gaps ω 1=2k¼0 versus relative temperature T=T N . Full circles denote the experimental data from a study by Keimer et al [33] Solid lines represent the theoretical result based on Equation (11). Figure 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-plane (dashed curve) and out-of-plane (full curve) zone-center energy gaps ω 1=2k¼0 versus relative temperature T=T N . Full circles denote the experimental data from a study by Keimer et al [33] Solid lines represent the theoretical result based on Equation (11). Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…Beside the nearest‐neighbor (NN) and next‐nearest‐neighbor (NNN) exchange interaction, it is often suggested that the description without taking into account the Dzyaloshinskii–Moriya (DM) interactions, [ 1,2 ] arising from spin–orbit coupling, may be considered as incomplete. [ 3–11 ] Namely, in La 2 CuO 4 , due to the spin–orbit couplings arising from the small orthorhombic distortion below the structural tetragonal–orthorhombic transition temperature Ttr=530 K, CuO 2 planes exhibit a weak ferromagnetic moment, i.e., all spins cant out of the CuO 2 plane by a small angle θ . However, this is not a common feature of the copper oxide layers as in the absence of the orthorhombic distortion DM interaction does not emerge (in Sr2CuO2Cl2, e.g.).…”
Section: Introductionmentioning
confidence: 99%
“…The next 31 P spectrum measurement was started always with decreasing magnetic field. The typical 31 P NMR spectra of the FeP single crys- α0( • ) B loc (T ) B1 -15.5(6) 0.851(9) B2 -14.4(5) 0.848(8) B3 -59.9(5) 0.841(8) B4 -60.0(4) 0.844 (5) talline sample measured at 140 MHz are presented in Fig. 10.…”
Section: B External Magnetic Field Rotated In the (Ac)-plane: High Fmentioning
confidence: 99%
“…Such a complex helicoidal magnetic structure is explained as a result of a competition of different isotropic (super)exchange interactions and/or anisotropic antisymmetric Dzyaloshinskii-Moriya coupling 4 (see, e.g., recent review article Ref. 5). It is worth noting that the use of circular polarized x-rays reveals a right-handed chirality in isostructural FeAs 6 that points to the antisymmetric Dzyaloshinskii-Moriya coupling to be main candidate to explain both a small canting for magnetic moments of Fe1, Fe2 (Fe3, Fe4) ions and spiral spin rotation in FeP.…”
Section: Introductionmentioning
confidence: 99%
“…[3], the authors of which performed first principles simulations for the structural, elastic, vibrational, electronic, and optical properties of orthorhombic samarium orthoferrite SmFeO 3 within the framework of density functional theory. However, such calculations encounter great difficulties in describing the more "subtle" effects of magnetic, magnetoelastic, and optical anisotropy [4].…”
Section: Introductionmentioning
confidence: 99%